Pemahaman Penggunaan PPE (Personal Protective Equipment) Pada Saat Kegiatan Tank Cleaning Di Kapal Mt. Success Marlina XXXIII - Muhammad Nur Riffa’i; Anak Agung Ngurah Ade Dwi Putra Yuda; Maulidiah Rahmawati; Mustamin Mustamin (Journal on Education, 2024)
Understanding the Use of PPE (Personal Protective Equipment) During Tank Cleaning Activities in MT. Success Marlina XXXIII. Supervised by Dr. Anak Agung Ngurah Ade Dwi Putra Yuda, S.Si.T., M.Pd., M.Mar. and Mrs. Maulidiah Rahmawati, S.Si., M.Sc. Tank cleaning needs to be done when the tanker changes cargo, this aims to prevent damage to the next cargo. Great attention is needed to human resources and the application of work discipline on board ships. In the book Safe Working Practice for Merchant Seafarers in chapter 8.3 there is an explanation of PPE which is personal protective equipment that is useful for reducing risks from various types of work including tank cleaning activities. Obtained from research results using the fishbone analysis method, researchers found that the crew of the MT. Success Marlina XXXIII does not fully understand or know about the rules and procedures for using PPE, this is because there is no drill regarding the use of PPE and there is no direction or notification from officers regarding the existing rules. The use of PPE when tank cleaning is not fully used properly, this happens because PPE spares are limited, there is no awareness regarding personal safety, the environment is hot, officers are less strict. It is recommended that the use of PPE be carried out optimally according to company regulations and the code of safe working practice for merchant seafarers in order to minimize work accidents.